2013
DOI: 10.12968/ijtr.2013.20.5.255
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles of allied health sciences students at Kuwait University

Abstract: Background/aim Little is known about learning style preferences of allied health students in the Middle East as the majority of learning style studies have been conducted in the western world. This study examined the learning styles of undergraduate allied health students at Kuwait University. Methods A stratified sampling method was used to compare the learning styles of 256 students enrolled in five allied health programs at the Faculty of Allied Health Sciences Centre at Kuwait University. The students comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Data gathered from the present study showed that there is a mismatch between the students' learning styles and multiple intelligences and the preferred teaching styles of EFL college teachers in Kuwait. In addition to Manee et al (2013), the present study provided fresh evidence on the majority of EFL college teachers in Kuwait as being teacher-centered. Therefore, college teachers are recommended to accommodate their students' learning styles and multiple intelligences in the classroom.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Data gathered from the present study showed that there is a mismatch between the students' learning styles and multiple intelligences and the preferred teaching styles of EFL college teachers in Kuwait. In addition to Manee et al (2013), the present study provided fresh evidence on the majority of EFL college teachers in Kuwait as being teacher-centered. Therefore, college teachers are recommended to accommodate their students' learning styles and multiple intelligences in the classroom.…”
Section: Discussionmentioning
confidence: 55%
“…The literature concerning learning styles and multiple intelligences especially among EFL college students presented two distinct bodies of evidence. While some EFL colleges have accommodated their students' learning styles and multiple intelligences, other EFL colleges were dominated by teachers who preferred the traditional teacher-centered method of teaching that promoted a classroom environment that did not accommodate students' learning styles and multiple intelligences (e.g., Abbasian & Shirazifard, 2016;Almigbal, 2015;Manee et al, 2013;Samarakoon et al, 2013;Winit-Watjana, et al, 2015). Data gathered from the present study showed that there is a mismatch between the students' learning styles and multiple intelligences and the preferred teaching styles of EFL college teachers in Kuwait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have been investigated student learning styles in different contexts, including mathematics (Akib, 2013), pharmacy (Crawford, Alhreish, & Popovich, 2012), EFL (English as a foreign language, Weng, 2012), health science (Manee, Nadar, & Jahrami, 2013), secondary schoolchildren (Ogundokun, 2011), medical students (Nuzhat, Salem, International Journal of Social Science Research ISSN 2327-5510 2013 Hamdan, & Ashour, 2013), business students (Ramayah, Sivanandan, Nasrijal, Letchumanan, & Lim Chee, 2009), and online-learning (Shaw, 2012). This survey of literature clear implies that the importance of learning styles of students for educators and practitioners to evaluate the appropriateness of pedagogies and curricula.…”
Section: Introductionmentioning
confidence: 99%